Application of method of multiple criteria analysis for establishing value/Daugiakriterinės nekilnojamojo turto analizės vertės nustatymo metodas ir jo taikymas - Malienė, Vida; Kaklauskas, Artūras; Zavadskas, Edmundas Kazimieras (Journal of Civil Engineering and Management, 2000)
Multiple criteria analysis presented in this paper for property valuation may be used to the advantage of various interested parties. The representatives of various parties including appraisers, buyers, sellers and investors may use it for their particular purposes: – appraiser may apply this method to real estate value analysis for determining the market, use and other values of real estate being mortgaged, ensured, privatised, divided or nationalised; – investor may rely on it for more efficient use of this property; – buyer may use it for choosing property which would satisfy his personal needs to the best advantage; – seller can use it for determining the market price of his property that would ensure its competitive ability on the market. To satisfy all the needs described, multiple criteria valuation method presented in the paper may be successfully applied. To show its efficiency, the solution of a sample problem representing a real case is provided.First Published Online: 26 Jul 2012